The Green building assessment tools for water efficiency criteria in Malaysia : an analysis / Halmi Zainol, Kartina Alauddin and Nadia Shukri - Halmi, Zainol; Kartina, Alauddin; Nadia, Shukri (Universiti Teknologi MARA, Perak, 2017)
It is conventionally accepted that the use of renewable resources has been in uncontrolled stage where the depletion of natural resources is increasing. inorder to be sustainable, the use of renewable resouces must be at the rate is less or equal to the rate of natural production. Therefore, there has been few efforts done by certain organisations to create awareness of sustainable built environment among the builders and public. Green assessment rating tools have been developed to act as a reference and guideline in order to create a sustainable development thus encourage a sustanable living. The objective of this paper is to evaluate the assessement criteria for green assessment tools. Fout rating tools consists of Green Building Index (GBI), penarafan Hijau JKR (pHJKR), Green Performance Assessment System (GreenPASS) and Green Real Estate (GreenRE) were selected. The finding shows on how assessment criteria of water efficiency can contribute to the sustainability life cycle thus redusing the depletion of natural resources. These rating tools also can contribute to the designers, builders and building owners during design and contruction stage to ensure the green building can be achieved.